Comparative analysis of expressed sequence tags from Malva pusilla, Sorghum bicolor, and Medicago truncatula infected with Colletotrichum species' - Goodwin, P.; Oliver, Richard; Hsiang, Y. (2004)
To assess relative gene expression, expressed sequence tag redundancy was compared between EST collections from susceptible Malva pusilla and Medicago truncatula inoculated with Colletotrichum gloeosporioides f. sp. malvae and C. trifolii, respectively, and resistant and susceptible Sorghum bicolor inoculated with C. graminicola (=C. sublineolum). EST redundancies from the fungal-inoculated S. bicolor and M. truncatula were also compared to healthy S. bicolor and M. truncatula. Several of the more redundant plant ESTs in the C. gloeosporioides f. sp. malvae–M. pusilla interaction represented genes encoding pathogenesis-related proteins, such as β-1,3-glucanase, osmotin and chitinase, but a number of other ESTs, such as those for cysteine proteinase, heat shock protein and glutathione S-transferase, were also relatively abundant. Differences in EST redundancy between different interactions included a greater abundance of heat shock protein ESTs in the susceptible S. bicolor interaction, and a greater abundance of cysteine proteinase ESTs in the resistant S. bicolor and susceptible M. truncatula interactions. Using EST redundancy to compare gene expression between different host plants interacting with Colletotrichum species provides a useful basis for selecting genes for further study in plant–Colletotrichum interactions.